1998
DOI: 10.1093/brain/121.12.2335
|View full text |Cite
|
Sign up to set email alerts
|

The role of DYT1 in primary torsion dystonia in Europe

Abstract: Primary torsion dystonia (PTD) is a clinically and genetically heterogeneous movement disorder. DYT1 on chromosome 9q34 was the first PTD gene to be mapped. A 3-bp (GAG) deletion in this gene was reported to account for almost all early limb-onset generalized PTD. No relationship has been found with DYT1 in patients with prominent craniocervical involvement. To elucidate the DYT1-associated phenotype, we analysed the DYT1 mutation in 150 PTD patients, either sporadic or index cases from small PTD families. Twe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
94
2
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(106 citation statements)
references
References 6 publications
8
94
2
2
Order By: Relevance
“…16 Solitary cases of DYT1-dystonia have been reported in studies where molecular analyses of the DNA of the parents were not done. 10,11 Apparently sporadic cases because of the low penetrance have also been reported earlier. 20 The difficulties in genetic counselling concerning dystonia is partly due to the low penetrance of many of the hereditary forms of dystonia and partly due to the variable phenotype within the same type of dystonia and, as shown in our study, the occurrence of de novo mutations.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…16 Solitary cases of DYT1-dystonia have been reported in studies where molecular analyses of the DNA of the parents were not done. 10,11 Apparently sporadic cases because of the low penetrance have also been reported earlier. 20 The difficulties in genetic counselling concerning dystonia is partly due to the low penetrance of many of the hereditary forms of dystonia and partly due to the variable phenotype within the same type of dystonia and, as shown in our study, the occurrence of de novo mutations.…”
Section: Discussionmentioning
confidence: 83%
“…10,11 DYT1-dystonia is by clinical and later also molecular genetic studies shown to be inherited as an autosomal, dominant trait with 30 ± 40% penetrance and localised on chromosome 9q34. 12 The gene encodes an ATP-binding protein, TorsinA.…”
Section: Introductionmentioning
confidence: 99%
“…We found an in-frame 3-bp deletion (GAG deletion), in TOR1-A gene, in two familial patients. To date, a GAG deletion in exon 5 of TOR1-A was related with almost all cases of DYT1 dystonia 3,4,5 . Our two patients with TOR1-A mutation presented typical DYT1 clinical features, with onset of symptoms by legs spraying to generalization, except for cervical involvement.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the patients DYT1 present generalization, caudal to rostral, in a time frame of 5 years. However, cranialcervical involvement has also been described as part of exceptional phenotypes of DYT1 dystonia, even focal or segmental disease 5,6,7,8 . We did not find DYT1 cases started by neck or staying in focal or segmental types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation